Bimetal site CoW-NC catalyst, preparation method and application thereof, and method for preparing dihydric alcohol from polyhydroxy compound
By developing a bimetal site CoW-NC catalyst, the problem of poor catalyst circulation is solved, efficient catalytic hydrogenolysis of polyhydroxy compounds is achieved, and a high yield of diol is obtained, and the catalyst has good cycle stability.
Patent Information
- Application Number
- CN202311353268.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-18
AI Technical Summary
In the prior art, the catalyst recycling ability is poor, resulting in difficulties in industrial application.
A bimetallic site CoW-NC catalyst was developed, formed by self-assembly of Co and W with nitrogen-doped porous carbon (NC), prepared by carbonization reduction method, with low active component loss rate and excellent cycle stability.
A one-pot catalytic hydrogenolysis of polyhydroxy compounds in the presence of hydrogen, water and catalyst was achieved, and excellent raw material conversion and diol yield were obtained, and the catalyst could be recycled multiple times.
Smart Images

Figure CN119857509A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic chemistry, and in particular to a bimetallic site CoW-NC catalyst and a preparation method and application thereof, and a method for preparing diols from polyhydroxy compounds. Background Art
[0002] Biomass-based chemicals can effectively avoid the shortcomings of traditional oil and gas routes such as fossil fuel dependence, high energy consumption, and high carbon dioxide emissions. At the same time, polyhydroxy biomass is widely present in nature, with abundant sources and easy to obtain. The route of preparing ethylene glycol by polyhydroxy biomass catalysis has the following advantages: 1. Good atom economy; 2. Easy to obtain raw materials; 3. Renewable resources; 4. Low carbon dioxide emissions. At present, the technology of preparing glycols by polyhydroxy biomass catalysis is not yet mature. Therefore, the development of new catalysts and new processes can promote the industrialization of this technology, thereby generating huge environmental and economic benefits.
[0003] CN105523890A directly uses glucose as raw material, and hydrolyzes and hydrogenates to prepare diols under the action of tungstate and alloy hydrogenation catalysts. This method requires alloys as co-catalysts, and the amount of metal used is large. In addition, tungstate needs to be added to the reaction system as a co-catalyst, and it will be lost with the solvent, resulting in poor catalyst recycling.
[0004] CN102190562A, CN101735014A and CN102731258A mainly use WC 2 and Ni nanoparticles as catalytic active components to convert glucose into ethylene glycol. However, the catalysts used in the above technologies have the problem of poor catalyst recycling, which brings great problems to practical industrial applications. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem of poor catalyst cycle stability in the prior art and to provide a new bimetallic site CoW-NC catalyst, which not only has good catalytic performance when used in catalytic reactions, such as the reaction of polyhydroxy biomass to produce diols, but also can obtain a higher yield of diols, and the catalyst has good cycle stability.
[0006] In order to achieve the above objectives, the first aspect of the present invention provides a new dual-metal site CoW-NC catalyst, which is a material formed by self-assembly of Co and W with nitrogen-doped porous carbon NC, and in the catalyst, Co is in a reduced state.
[0007] The second aspect of the present invention provides a method for preparing the bimetallic site CoW-NC catalyst of the present invention, the preparation method comprising: carbonizing and reducing a metal organic framework material containing W and Co bimetallics to obtain a bimetallic site CoW-NC catalyst; wherein the conditions for the carbonization reduction include: the carbonization temperature is greater than 150°C.
[0008] The third aspect of the present invention provides use of the catalyst of the present invention in catalytic hydrogenolysis of polyhydroxy compounds.
[0009] A fourth aspect of the present invention provides a method for preparing diols from polyhydroxy compounds, the method comprising: catalytic hydrogenolysis of the polyhydroxy compounds in the presence of hydrogen, water and the catalyst of the present invention.
[0010] Through the above technical scheme, the metal active components of the catalyst provided by the present invention are not easy to be lost. In the presence of the catalyst of the present invention, polyhydroxy compounds are used to prepare diols in one pot, which can achieve excellent comprehensive effects of raw material conversion rate and diol yield, and the catalyst can also be recycled for multiple times. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 is a SEM electron microscope image of the catalyst in Example 1;
[0012] Figure 2 is the XRD spectra of the catalysts in Example 1 and Comparative Example 2;
[0013] Figure 3 Example 1 is the XPS spectrum of the catalyst in Example 1. DETAILED DESCRIPTION
[0014] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0015] In a first aspect, the present invention provides a novel dual-metal site CoW-NC catalyst. The dual-metal site CoW-NC catalyst is a material formed by self-assembly of Co and W together with nitrogen-doped porous carbon NC.
[0016] In the present invention, nitrogen-containing metal organic framework materials (MOFs) are precursors of NC; CoW-NC refers to a periodic three-dimensional porous crystalline material formed by self-assembly of Co and W together with nitrogen-doped porous carbon NC, that is, a material formed after carbonization derivatization; CoW-NC catalyst has the advantages of low loss rate of active components and excellent cycle stability; wherein Co and W can exist in the form of a single substance or in the form of a compound (such as an oxide), preferably, Co is in a reduced state (that is, Co exists in the form of an element). The catalyst under the aforementioned preferred embodiment is more conducive to improving the catalytic performance of the catalyst.
[0017] According to the present invention, in some embodiments, in the catalyst, the chemical valence state of W is +6. The catalyst in the aforementioned embodiment has a more excellent catalytic performance, and when used for catalytic hydrogenolysis of polyhydroxy compounds, a better comprehensive effect of feedstock conversion rate and diol selectivity can be obtained.
[0018] In the present invention, the valence state of the metal elements in the catalyst is characterized by X-ray photoelectron spectroscopy.
[0019] According to the present invention, in some embodiments, the particle size of the catalyst is 30-1000nm, for example, 30nm, 40nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 700nm, 1000nm, or a range consisting of any two of the above values, preferably 30-200nm. The catalyst under the above embodiment has good uniformity and can greatly improve the catalytic activity and catalytic stability of the catalyst in the reaction.
[0020] According to the present invention, in some embodiments, the specific surface area of the catalyst is 20-400m 2 g -1 , for example 20m 2 g -1 、30m 2 g -1 、40m 2 g -1 、50m 2 g -1 、60m 2 g -1 、100m 2 g -1 、150m 2 g -1 、160m 2 g -1 、200m 2 g -1 、250m 2 g -1 、300m 2 g-1 、400m 2 g -1 , preferably 50-150m 2 g -1 The catalyst in the aforementioned embodiment can greatly improve the catalytic activity of the catalyst in the reaction.
[0021] In the present invention, it should be noted that when preparing a catalyst, a certain amount of catalyst is generally prepared, and the particle size and / or specific surface area of the prepared catalyst may be a fixed value or a range value, generally a range value, that is, the particle size of the catalyst is a range value consisting of the maximum size and the minimum size in a field of view on XRD, and the specific surface area of the catalyst is a range value consisting of the maximum specific surface area and the minimum specific surface area in the prepared catalyst.
[0022] According to the present invention, it can be understood that the catalyst of the present invention includes metal parts Co, W and non-metal parts NC. In some embodiments, the mass ratio of the metal parts Co, W and non-metal parts NC in the catalyst is (0.8-10): 1, preferably (0.85-2): 1. The catalyst under the above embodiment has a more stable structure.
[0023] In the catalyst, Co is calculated as Co element, W is calculated as W element, and the mass ratio of Co to W is 1-2:1, for example, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.5:1, 1.6:1, 2:1, or any range of the above values. The catalyst under the above embodiment can greatly improve the catalytic activity and stability of the catalyst in the reaction.
[0024] In the present invention, the content of the elements can be tested by ICP.
[0025] In the present invention, as mentioned above, metal organic framework materials (MOFs) are the precursors of NC. The second aspect of the present invention provides a method for preparing the bimetallic site CoW-NC catalyst described in the present invention, and the preparation method comprises: carbonizing and reducing a nitrogen-containing metal organic framework material containing W and Co bimetallics to obtain a bimetallic site CoW-NC catalyst; wherein the conditions for the carbonization reduction include: the carbonization temperature is greater than 150°C.
[0026] The catalyst preparation method provided by the present invention uses nitrogen-containing metal organic framework materials (MOFs) containing W and Co bimetallics to perform carbonization reduction at a certain carbonization temperature. The prepared catalyst has excellent catalytic performance and stability. Not only can it be used to directly use one-pot catalytic hydrogenolysis to prepare diols when used to prepare diols, but also can obtain excellent comprehensive effects of raw material conversion rate and diol selectivity. At the same time, the catalyst has good recyclability.
[0027] According to the present invention, in some embodiments, the carbonization reduction conditions include: performing carbonization reduction in a reducing atmosphere containing hydrogen.
[0028] According to the present invention, in some preferred embodiments, the reducing atmosphere comprises 5-30% by volume of hydrogen, and the remainder is an inert gas (such as nitrogen or argon, preferably nitrogen). The catalyst prepared by the above embodiment can obtain a better comprehensive effect of feedstock conversion rate and diol selectivity when used for catalytic hydrogenolysis of polyhydroxy compounds.
[0029] According to the present invention, in some embodiments, the carbonization reduction conditions include: the carbonization temperature is 200-600°C, for example, 100°C, 250°C, 300°C, 400°C, 500°C, 600°C, or any range of the above values, preferably 250-500°C, more preferably 300-500°C; the preferred carbonization time is 1-24h, preferably 2-10h. By adopting the above embodiment, the role of the fixed metal element valence state in the preparation process can be fully utilized, and the prepared catalyst has better catalytic performance. When using it in the catalytic hydrogenolysis of polyhydroxy compounds, a better comprehensive effect of raw material conversion rate and diol selectivity can be obtained.
[0030] In the present invention, the metal organic framework material containing W and Co bimetallic refers to a periodic three-dimensional porous crystalline material formed by self-assembly of W and Co metal ions and organic ligands. In some embodiments, the preparation method of the metal organic framework material containing W and Co bimetallic includes: performing a solvothermal reaction in a raw material mixture containing Co source, W source and nitrogen-containing organic ligands. By adopting the above-mentioned embodiment, a metal organic framework material containing W and Co bimetallic with excellent performance can be obtained.
[0031] According to the present invention, in some preferred embodiments, the conditions of the solvothermal reaction include: the reaction temperature is 100-180° C., preferably 120-160° C. By adopting the above embodiment, a W and Co bimetallic metal organic framework material with excellent performance can be obtained, and the prepared catalyst has excellent catalytic activity and stability.
[0032] According to the present invention, in some preferred embodiments, the conditions of the solvothermal reaction include: the reaction time is 24-240h, preferably 48-168h. By adopting the above-mentioned embodiment, a W and Co bimetallic metal organic framework material with excellent performance can be obtained, and the prepared catalyst has excellent catalytic activity and stability.
[0033] According to the present invention, the device for performing the solvothermal reaction is not limited and can be any device capable of performing the solvothermal reaction in the art. For example, the solvothermal reaction is performed in a tetrafluoroethylene autoclave and heating can be achieved using an oven.
[0034] According to the present invention, solvent and / or unreacted raw materials may still exist in the raw material mixture after the solvent thermal reaction. In some embodiments, the preparation method of the W and Co bimetallic organic framework materials further includes: washing and drying the solid material obtained by the solvent thermal reaction; wherein the solid material obtained by the solvent thermal reaction can be obtained by separation and filtration. In the present invention, there is no limitation on the aforementioned washing method, as long as the washing purpose can be achieved, for example, using low-boiling point solvents such as ethanol and acetone and water for washing 2-5 times respectively; drying can be achieved in a drying oven, for example, drying in a drying oven at 60-90°C for 10-30h.
[0035] According to the present invention, as long as the purpose of the present invention can be achieved, the type of Co source is not limited, as long as it can provide Co ions for the metal organic framework material. In some embodiments, the Co source is selected from at least one of cobalt acetate, cobalt nitrate, cobalt chloride and cobalt sulfate.
[0036] According to the present invention, the type of W source is not limited as long as the purpose of the present invention can be achieved, as long as it can provide W ions for the metal organic framework material. In some embodiments, the W source is selected from at least one of tungstic acid, ammonium metatungstate and tungsten oxide.
[0037] According to the present invention, in some embodiments, the nitrogen-containing organic ligand includes 2-methylimidazole. By adopting the above embodiment, a catalyst with better performance can be finally obtained.
[0038] According to the present invention, the raw material mixed liquid containing Co source, W source and nitrogen-containing organic ligand refers to a raw material mixed liquid obtained by mixing the raw materials including Co source, W source, nitrogen-containing organic ligand and solvent. The mixing method is not particularly limited and the raw material mixed liquid can be obtained by ultrasonicating the Co source, W source, nitrogen-containing organic ligand and solvent for 0.2-2h.
[0039] According to the present invention, as long as the purpose of the present invention can be achieved, the solvent in the raw material mixture can be selected from a wide range. In some embodiments, the solvent in the raw material mixture is selected from an aprotic solvent. The above-mentioned embodiment is conducive to improving the catalytic activity of the catalyst, and when it is used for catalytic hydrogenolysis of polyhydroxy compounds, a better comprehensive effect of raw material conversion rate and diol selectivity can be obtained.
[0040] According to the present invention, in some preferred embodiments, the solvent in the raw material mixture is at least one of N,N-dimethylformamide, dimethyl sulfoxide, and N,N-dimethylacetamide, preferably N,N-dimethylformamide. The above embodiment is beneficial to improving the catalytic activity of the catalyst, and when it is used for catalytic hydrogenolysis of polyhydroxy compounds, a better comprehensive effect of raw material conversion rate and diol selectivity can be obtained.
[0041] According to the present invention, in some embodiments, the Co source is calculated as Co element and the W source is calculated as W element, and the mass ratio of the Co source to the W source is 0.25-4:1, preferably 1-2:1. The above embodiment is used to improve the catalytic activity of the catalyst, and when it is used for catalytic hydrogenolysis of polyhydroxy compounds, a better comprehensive effect of raw material conversion rate and diol selectivity can be obtained.
[0042] According to the present invention, in some embodiments, the Co source is calculated as Co element and the W source is calculated as W element, and the mass ratio of the total mass of the Co source and the W source to the organic ligand is 0.15-24:1, preferably 1-10:1.
[0043] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of solvent in the raw material mixture is not particularly limited, as long as the solvent thermal reaction can proceed smoothly. In some embodiments, the total mass of the Co source, the W source, and the organic ligand in the solvent is 0.0025-1.7 g / mL, preferably 0.01-0.1 g / mL.
[0044] The third aspect of the present invention provides use of the catalyst of the present invention in catalytic hydrogenolysis of polyhydroxy compounds.
[0045] In the present invention, the catalyst of the present invention is used to carry out catalytic hydrogenolysis of polyhydroxy compounds, which not only has good catalytic performance, but also has good cycle stability.
[0046] A fourth aspect of the present invention provides a method for preparing diols from polyhydroxy compounds, the method comprising: catalytic hydrogenolysis of the polyhydroxy compounds in the presence of hydrogen, water and the catalyst of the present invention.
[0047] In the present invention, the use of the catalyst of the present invention for catalytic hydrogenolysis of polyhydroxy compounds can not only achieve a better comprehensive effect of feedstock conversion rate and diol selectivity, but also the catalyst has good recyclability.
[0048] According to the present invention, there is no particular limitation on the amounts of hydrogen, water, catalyst and polyol, as long as they are conducive to the catalytic hydrogenolysis reaction of the polyol.
[0049] According to the present invention, in some embodiments, the mass ratio of the polyhydroxy compound to the catalyst is 10-0.1:1, preferably 0.5-5:1.
[0050] According to the present invention, in some embodiments, the mass ratio of water to polyhydroxy compound is 4-1000:1, preferably 10-100:1.
[0051] According to the present invention, in some embodiments, the amount of hydrogen introduced is such that the reaction pressure is 0.5-10 MPa, preferably 1-6 MPa.
[0052] According to the present invention, the specific type of the polyhydroxy compound is not particularly limited, as long as it can obtain diols through catalytic hydrogenolysis reaction. In some embodiments, the polyhydroxy compound includes at least one of cellulose, glucose, fructose and sorbitol.
[0053] According to the present invention, those skilled in the art can understand that the prepared diol includes at least one of ethylene glycol, 1,2-propylene glycol, and 1,2-butanediol.
[0054] According to the present invention, in some embodiments, the conditions for the catalytic hydrogenolysis include: a reaction temperature of 150-300°C, preferably 200-245°C.
[0055] According to the present invention, in some embodiments, the conditions for the catalytic hydrogenolysis include: the reaction time is 0.5-12h, preferably 0.5-4h.
[0056] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:
[0057] Glucose to diols: 0.075g catalyst, 0.25g glucose and 25mL deionized water were added to a stirred autoclave, hydrogen was introduced for replacement three times, and then hydrogen was filled to 4MPa and sealed. The temperature was raised to 245°C by a programmed heating jacket, and then stirred by magnetic stirring; the reaction was carried out at 245°C for 1h, and the product in the reaction solution was quantitatively analyzed by gas chromatography, and the raw materials in the reaction solution were quantitatively analyzed by liquid chromatography. The conversion rate of glucose, the yield of diols and the selectivity of diols were calculated according to the following formula.
[0058] The reaction product diols (e.g., ethylene glycol, propylene glycol, butanediol) were qualitatively analyzed by gas chromatography-mass spectrometry (GC-MS), and the yield of the product diols (e.g., ethylene glycol, propylene glycol, butanediol) and the conversion rate of the reaction substrate glucose were analyzed by gas chromatography (GC). The gas chromatography-mass spectrometry instrument was Agilent 7890A of Agilent, USA, the chromatographic column was HP-5 non-polar capillary column (30m, 0.53mm), the gas chromatograph was Agilent 7890B, the detector was a hydrogen flame ionization detector (FID), and the chromatographic column was HP-INNOWAX capillary column (60m, 0.25mm).
[0059] Recyclability: The catalyst used in the production of glucose into diols was washed three times with ethanol and deionized water respectively, and then dried and recycled for next reaction. The next reaction was continued according to the above reaction conditions for the production of glucose into diols. The cycle was repeated several times. The conversion rate of glucose, the yield of diols and the selectivity of diols were calculated according to the following formulas.
[0060] Glucose conversion rate (%) = (molar amount of glucose participating in the reaction) / (molar amount of glucose as the initial reaction substrate) × 100%.
[0061] The product diol (ethylene glycol, propylene glycol, butanediol) yield calculation formula is:
[0062] The yield of the product diol (%) = (the number of carbon atoms corresponding to the molar amount of the diol generated by the reaction) / (the number of carbon atoms corresponding to the molar amount of the initial reaction substrate glucose) × 100%.
[0063] Selectivity of product diol (%) = (the number of carbon atoms corresponding to the molar amount of diol produced by the reaction) / (the molar amount of glucose participating in the reaction) × 100%.
[0064] Example 1
[0065] Preparation of bimetallic site CoW-NC catalysts:
[0066] (1) 0.199 g of cobalt acetate tetrahydrate, 0.096 g of 2-methylimidazole, 0.05 g of tungstic acid and 4 mL of N,N-dimethylformamide were added to a 20 mL tetrafluoroethylene autoclave, ultrasonicated for half an hour, and then placed in an oven and heated to 160° C. for 144 hours; after the device was cooled to room temperature, it was separated and filtered to obtain a blue crystalline product, which was washed three times with ethanol and deionized water respectively, and dried in a drying oven at 80° C. for 18 hours to obtain a metal organic framework material containing W and Co bimetallics;
[0067] (2) The obtained W and Co bimetallic metal organic framework material was heated to 450°C in a hydrogen atmosphere and calcined for 2 hours to obtain a bimetallic site CoW-NC catalyst.
[0068] The SEM images of the catalyst are shown in Figure 1 As shown, through Figure 1 The particle size of the catalyst can be obtained to be 30-200nm;
[0069] The specific surface area of the catalyst is 50-150m 2 g -1 ;
[0070] In the catalyst, Co is 0 valence, W is +6 valence; the content of Co is 30wt%, the content of W is 24wt%, and the content of NC is 46wt%;
[0071] The XRD spectrum of the catalyst is as follows Figure 2 As shown, it indicates that the Co element is mainly loaded on NC in the form of 0-valent nanoparticles;
[0072] The XPS spectrum of the catalyst is shown in Figure 3 As shown, it indicates that the W element does not exist on NC in the form of nanoparticles, but is loaded on NC in the form of +6 valence.
[0073] In the experiment of using it to prepare glycols from glucose, the conversion rate of glucose was greater than 99%; the yield of glycols was 43%, the selectivity of ethylene glycol was 15.8%, the selectivity of 1,2-propylene glycol was 20.2%, and the selectivity of 1,2-butanediol was 7.2%; the catalyst was recycled 4 times, and the conversion rate of glucose was greater than 99% in the 4 reactions; the yields of glycols in the 1st to 4th reactions were 43%, 41.5%, 41% and 42.1%, respectively.
[0074] Example 2
[0075] The method of Example 1 is followed, except that in step (1), N,N-dimethylformamide is replaced by dimethyl sulfoxide, and finally a bimetallic site CoW-NC catalyst is obtained.
[0076] SEM images of the catalyst and Figure 1 Similarly, the particle size of the catalyst is 30-200 nm;
[0077] The specific surface area of the catalyst is 50-150m 2 g -1 ;
[0078] In the catalyst, Co is 0 valence, W is +6 valence; the content of Co is 28 wt%, the content of W is 23 wt%, and the content of NC is 49 wt%.
[0079] In the experiment of using it to produce glycols from glucose, the conversion rate of glucose was greater than 99%; the yield of glycols was 41.2%, the selectivity of ethylene glycol was 15.3%, the selectivity of 1,2-propylene glycol was 18.9%, and the selectivity of 1,2-butanediol was 7%.
[0080] Example 3
[0081] The method of Example 1 is followed, except that in step (2), the obtained metal organic framework material containing W and Co bimetallics is heated to 300° C. under a hydrogen atmosphere to finally obtain a bimetallic site CoW-NC catalyst.
[0082] SEM images of the catalyst and Figure 1 Similarly, the particle size of the catalyst is 100-1000nm;
[0083] The specific surface area of the catalyst is 150-400m 2 g -1 ;
[0084] In the catalyst, Co is 0 valence, W is +6 valence; the content of Co is 25 wt%, the content of W is 20 wt%, and the content of NC is 55 wt%.
[0085] In the experiment of using it to produce glycols from glucose, the conversion rate of glucose was greater than 99%; the yield of glycols was 37.2%, the selectivity of ethylene glycol was 13.2%, the selectivity of 1,2-propylene glycol was 17.3%, and the selectivity of 1,2-butanediol was 6.7%.
[0086] Example 4
[0087] The method of Example 1 is followed, except that in step (2), the obtained metal organic framework material containing W and Co bimetallics is heated to 600° C. under a hydrogen atmosphere to finally obtain a bimetallic site CoW-NC catalyst.
[0088] SEM images of the catalyst and Figure 1 Similarly, the particle size of the catalyst is 30-200 nm;
[0089] The specific surface area of the catalyst is 30-100m 2 g -1 ;
[0090] In the catalyst, Co is 0 valence, W is +6 valence; the content of Co is 40 wt%, the content of W is 32 wt%, and the content of NC is 28 wt%.
[0091] In the experiment of using it to produce glycol from glucose, the conversion rate of glucose was greater than 99% and the yield of glycol was 35.8%.
[0092] Example 5
[0093] The method of Example 1 is followed, except that in step (2), the obtained metal organic framework material containing W and Co bimetallics is heated to 800° C. under a hydrogen atmosphere to finally obtain a bimetallic site CoW-NC catalyst.
[0094] SEM images of the catalyst and Figure 1 Similarly, the particle size of the catalyst is 30-200 nm;
[0095] The specific surface area of the catalyst is 30-100m 2 g -1 ;
[0096] In the catalyst, Co is 0 valent, W is +6 valent; the content of Co is 46 wt%, the content of W is 36 wt%, and the content of NC is 18 wt%.
[0097] In the experiment of using it to produce glycol from glucose, the conversion rate of glucose was greater than 99% and the yield of glycol was 28.1%.
[0098] Example 6
[0099] The method of Example 1 was followed, except that in step (1), "0.199 g of cobalt acetate tetrahydrate, 0.096 g of 2-methylimidazole, 0.05 g of tungstic acid and 4 mL of N,N-dimethylformamide were added to a 20 mL tetrafluoroethylene autoclave" was replaced by 1 g of cobalt acetate tetrahydrate, 0.480 g of 2-methylimidazole, 0.250 g of tungstic acid and 20 mL of N,N-dimethylformamide were added to a 100 mL tetrafluoroethylene autoclave, and finally a bimetallic site CoW-NC catalyst was obtained.
[0100] SEM images of the catalyst and Figure 1 Similarly, the particle size of the catalyst is 30-200 nm;
[0101] The specific surface area of the catalyst is 50-150m 2 g -1 ;
[0102] In the catalyst, Co is 0 valence, W is +6 valence; the content of Co is 30 wt%, the content of W is 24 wt%, and the content of NC is 46 wt%.
[0103] In the experiment of using it to produce glycol from glucose, the conversion rate of glucose was greater than 99% and the yield of glycol was 42.7%.
[0104] Example 7
[0105] The method of Example 1 was followed, except that in step (1), "0.199 g of cobalt acetate tetrahydrate, 0.096 g of 2-methylimidazole, 0.05 g of tungstic acid and 4 mL of N,N-dimethylformamide were added to a 20 mL tetrafluoroethylene autoclave" was replaced by 3 g of cobalt acetate tetrahydrate, 0.480 g of 2-methylimidazole, 0.250 g of tungstic acid and 20 mL of N,N-dimethylformamide were added to a 100 mL tetrafluoroethylene autoclave, and finally a bimetallic site CoW-NC catalyst was obtained.
[0106] SEM images of the catalyst and Figure 1 Similarly, the particle size of the catalyst is 50-100 nm;
[0107] The specific surface area of the catalyst is 50-150m 2 g -1 ;
[0108] In the catalyst, Co is 0 valence, W is +6 valence; the content of Co is 50 wt%, the content of W is 12 wt%, and the content of NC is 38 wt%.
[0109] In the experiment of using it to produce glycol from glucose, the conversion rate of glucose was greater than 99% and the yield of glycol was 35.3%.
[0110] Example 8
[0111] The method of Example 1 is followed, except that in step (2), "heating to 450°C in a hydrogen atmosphere" is replaced by heating to 450°C in a hydrogen-argon mixed gas atmosphere containing 10 vol% hydrogen, to finally obtain a bimetallic site CoW-NC catalyst.
[0112] SEM images of the catalyst and Figure 1 Similarly, the particle size of the catalyst is 30-200 nm;
[0113] The specific surface area of the catalyst is 50-150m 2 g -1 ;
[0114] In the catalyst, Co is 0 valent, and W is +6 valent; the content of Co is 24 wt%, the content of W is 23 wt%, and the content of NC is 53 wt%.
[0115] In the experiment of using it to produce glycols from glucose, the conversion rate of glucose was greater than 99%; the yield of glycols was 50%; the catalyst was recycled 4 times, and in the 4 reactions, the conversion rate of glucose was greater than 99%; the yields of glycols in the 1st to 4th reactions were 50%, 49.6%, 48.2% and 48%, respectively.
[0116] Comparative Example 1
[0117] 0.05g of tungstic acid and 0.199g of cobalt acetate tetrahydrate were heated and dissolved in 3mL of deionized water, and ultrasonicated for half an hour. The above solution was added to 0.5g of activated carbon, shaken until mixed evenly, and placed in an 80℃ drying oven for 8-12h. The obtained sample was heated to 400℃ in a hydrogen atmosphere and calcined for 1-3h to obtain a CoW / AC catalyst.
[0118] The specific surface area of the catalyst is 800m 2 g -1 ;
[0119] In the catalyst, Co is 0 valent, W is +6 valent; the content of Co is 12 wt%, the content of W is 9 wt%, and the content of activated carbon AC is 79 wt%.
[0120] In the experiment of using the catalyst to produce glycols from glucose, the conversion rate of glucose was greater than 99%; the yield of glycols was 10.4%, the selectivity of ethylene glycol was 6.8%, the selectivity of 1,2-propylene glycol was 3.4%, and the selectivity of 1,2-butanediol was 0.2%.
[0121] Comparative Example 2
[0122] 0.199g of cobalt acetate tetrahydrate, 0.096g of 2-methylimidazole, 0.05g of tungstic acid and 4mL of N,N-dimethylformamide were added to a 20mL tetrafluoroethylene autoclave, ultrasonicated for half an hour, and then placed in an oven and heated to 160°C for 144 hours; after the device was cooled to room temperature, a blue crystalline product was obtained, which was washed three times with ethanol and deionized water respectively, and placed in an 80°C drying oven for 18 hours. The HZIF-CoW catalyst was obtained.
[0123] The particle size of the catalyst is 5000-10000nm;
[0124] The specific surface area of the catalyst is 400m 2 g -1 ;
[0125] The XRD spectrum of the catalyst is as follows Figure 2 As shown, it indicates that the Co element is not loaded on NC in the form of 0-valent nanoparticle coordination;
[0126] In the catalyst, Co is +2 valence, W is +6 valence; the content of Co is 23 wt%, the content of W is 18 wt%, and the content of NC is 59 wt%.
[0127] In the experiment of using the catalyst to produce glycols from glucose, the conversion rate of glucose was greater than 99%, the yield of glycols was 0.3%, the selectivity of ethylene glycol was 0.1%, the selectivity of 1,2-propylene glycol was 0.2%, and the selectivity of 1,2-butanediol was 0%.
[0128] Comparative Example 3
[0129] The method of Example 1 is followed, except that in step (2), the obtained metal organic framework material containing W and Co bimetallics is heated to 150° C. under a hydrogen atmosphere to finally obtain a bimetallic site CoW-NC catalyst.
[0130] SEM images of the catalyst and Figure 1 Similarly, the particle size of the catalyst is 1000-10000nm;
[0131] The specific surface area of the catalyst is 300-400m 2 g -1 ;
[0132] In the catalyst, Co is +2 valence, W is +6 valence; the content of Co is 23 wt%, the content of W is 18 wt%, and the content of NC is 59 wt%.
[0133] In the experiment of using the catalyst to produce glycols from glucose, the conversion rate of glucose was greater than 99%; the yield of glycols was 9.1%, the selectivity of ethylene glycol was 3%, the selectivity of 1,2-propylene glycol was 4.2%, and the selectivity of 1,2-butanediol was 1.9%.
[0134] Comparative Example 4
[0135] Preparation of Bimetallic Site ZnW-NC Catalysts:
[0136] (1) 0.176 g zinc acetate dihydrate, 0.096 g 2-methylimidazole, 0.05 g tungstic acid and 4 mL N, N-dimethylformamide were added to a 20 mL tetrafluoroethylene autoclave, ultrasonicated for half an hour, and then placed in an oven and heated to 160°C for 144 hours. After the device was cooled to room temperature, a colorless crystalline product was obtained, which was washed three times with ethanol and deionized water respectively, and dried in an 80°C drying oven for 18 hours to obtain a metal organic framework material containing Zn and W bimetallics;
[0137] (2) The obtained Zn and W bimetallic metal organic framework material was heated to 450°C in a hydrogen atmosphere and calcined for 2 hours to obtain a bimetallic site ZnW-NC catalyst.
[0138] The particle size of the catalyst is 1000 nm;
[0139] The specific surface area of the catalyst is 100-200m 2 g -1 ;
[0140] In the catalyst, Zn is 0 valence, W is +6 valence; the content of Zn is 29wt%, the content of W is 23wt%, and the content of NC is 48wt%;
[0141] In the experiment of using the catalyst to produce diols from glucose, the conversion rate of glucose was greater than 99% and the yield of diols was 0.5%.
[0142] It can be seen from the results of the above examples and comparative examples that the catalyst of the present invention has good catalytic performance, and when it is used to carry out catalytic hydrogenolysis of polyhydroxy compounds, a better comprehensive effect of conversion rate and diol selectivity can be obtained.
[0143] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A dual metal site CoW-NC catalyst, characterized in that: The dual-metal site CoW-NC catalyst is a material formed by self-assembly of Co and W together with nitrogen-doped porous carbon NC, and in the catalyst, Co is in a reduced state.
2. The catalyst according to claim 1, wherein In the catalyst, the chemical valence state of W is +6; and / or The particle size of the catalyst is 30-1000 nm, preferably 30-200 nm; and / or The specific surface area of the catalyst is 20-400m 2 g -1 .
3. The catalyst according to claim 1 or 2, wherein In the catalyst, the mass ratio of the metal part Co, W to the non-metal part NC is 0.8-10:1, preferably 0.85-2:1, calculated as the metal part in terms of elements; and / or In the catalyst, Co is calculated as Co element, W is calculated as W element, and the mass ratio of Co to W is 1-2:
1.
4. A method for preparing a bimetallic site CoW-NC catalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises: carbonizing and reducing a nitrogen-containing metal organic framework material containing W and Co bimetallics to obtain a bimetallic site CoW-NC catalyst; Wherein, the carbonization reduction conditions include: the carbonization temperature is greater than 150°C.
5. The preparation method according to claim 4, wherein: The carbonization reduction conditions include: Carrying out carbonization reduction in a reducing atmosphere containing hydrogen, preferably the reducing atmosphere comprises 5-30 volume % hydrogen and the remainder is an inert gas; and / or; The carbonization temperature is 200-600°C, preferably 250-500°C; and / or The carbonization time is 1-24 hours, preferably 2-10 hours.
6. The preparation method according to claim 4 or 5, wherein: The preparation method of the W-Co bimetallic organic framework material comprises: performing a solvothermal reaction in a raw material mixture containing a Co source, a W source and a nitrogen-containing organic ligand; Preferably, the conditions of the solvent thermal reaction include: a reaction temperature of 100-180°C, preferably 120-160°C; and / or a reaction time of 24-240h, preferably 48-168h; and / or The preparation method of the W- and Co-containing bimetallic organic framework material further comprises: washing and drying the solid material obtained by the solvent thermal reaction.
7. The preparation method according to claim 6, wherein: The Co source is selected from at least one of cobalt acetate, cobalt nitrate, cobalt chloride and cobalt sulfate; and / or The W source is selected from at least one of tungstic acid, ammonium metatungstate and tungsten oxide; and / or The nitrogen-containing organic ligand comprises 2-methylimidazole; and / or The solvent in the raw material mixture is selected from aprotic solvents, preferably at least one of N,N-dimethylformamide, dimethyl sulfoxide, and N,N-dimethylacetamide, and more preferably N,N-dimethylformamide and / or dimethyl sulfoxide.
8. The preparation method according to claim 6 or 7, wherein: The Co source is calculated as Co element, and the W source is calculated as W element, and the mass ratio of the Co source to the W source is 0.25-4:1, preferably 1-2:1; and / or The Co source is calculated as Co element, and the W source is calculated as W element. The mass ratio of the total mass of the Co source and the W source to the organic ligand is 0.15-24:1, preferably 1-10:
1.
9. Use of the catalyst according to any one of claims 1 to 3 in the catalytic hydrogenolysis of polyhydroxy compounds.
10. A method for preparing diols from polyhydroxy compounds, characterized in that: The method includes: The polyhydroxy compound is subjected to catalytic hydrogenolysis in the presence of hydrogen, water and the catalyst according to any one of claims 1 to 3; Preferably, the mass ratio of the polyol to the catalyst is 10-0.1:1, preferably 0.5-5:1; and / or The mass ratio of water to polyhydroxy compound is 4-1000:1, preferably 10-100:1; and / or The amount of hydrogen introduced is such that the reaction pressure is 0.5-10 MPa, preferably 1-6 MPa; and / or The polyol comprises at least one of cellulose, glucose, fructose and sorbitol; and / or The conditions for the catalytic hydrogenolysis include: a reaction temperature of 150-300° C., preferably 200-245° C.; and / or a reaction time of 0.5-12 h, preferably 0.5-4 h.
Citation Information
Patent Citations
Method for preparing ethanediol from polyhydroxy compounds
CN101735014A
Method for preparing ethylene glycol from polyols
CN102190562A
Method for preparing low carbon polyol by internal circulating catalysis and conversion of carbohydrate
CN102731258A
Method for preparing dihydric alcohol
CN105523890A
Nitrogen functional carbon material loaded with transition metal chalcogenide as well as preparation and application of nitrogen functional carbon material
CN106111177A